Czego (nie) boi się surrealizm? Przerażająca (nad)rzeczywistość twórczych koszmarów surrealistów i surrealistek - Magdalena Piotrowska-Grot (Zagadnienia Rodzajów Literackich)
Surrealism brings dreams into literature, turning them into a field of artistic exploration, often revolving around nightmares. Inspired by Freud’s ideas, surrealists viewed dreams as a space of freedom where the rules of reality do not apply. In the Manifesto of Surrealism, André Breton emphasized that in dreams, one experiences true liberation — one can love, kill, fly, die, and resurrect. For surrealists, dreams were not merely a form of artistic expression but also a means of transcending social and cultural boundaries. Artistic experiments conducted by (neo)surrealist artists frequently transgress established moral and aesthetic norms. The ostensibly “innocent” beginnings — such as the recording of dreams, the induction of hallucinations, surrendering to trance states, or evoking visions through the use of intoxicants — gradually evolved into artistic creations that often bordered on the morally and ethically contentious. Gherasim Luca, for instance, envisioned corporeal punishments inflicted upon his antagonists, while Max Ernst and Hans Bellmer produced works depicting female bodies subjected to acts of torture. In contrast to this dominant current, women surrealist artists developed an oppositional practice — within their dreamlike visions, they emancipated their female protagonists from the constraints of patriarchy and the socially imposed roles assigned to them. The demons of dreams, considered natural and primal, merge with waking reality, and recording these experiences was intended not only to shock but also to free both artists and audiences from conventions. Surrealism was not limited to a revolution in art — it sought to break norms and dismantle social structures. This text, analyzing selected works of surrealists, will explore the boundaries of these experiments and whether these “nightmarish” explorations reveal what surrealist artists were truly afraid of.